The African Union’s Policy Frameworks, Institutional Mechanisms and Challenges in Countering Terrorism in Africa - Mensah, Isaac (Terrorism and political violence, 2023)
This article discusses the normative framework and institutional mechanisms for African counterterrorism cooperation. These frameworks have been discussed in sequential order showing how they relate to and complement each other in their efforts to counter terrorism in Africa. The first section focuses on the evolution of the counterterrorism agenda in Africa from 1992 to 1994. The second part discusses the main African Union (AU) counterterrorism legislative framework whereas the third section discusses the institutional mechanisms provided by the 2004 Protocol for the implementation of the provisions of the OAU Convention. Finally, the article discusses the challenges of the AU counterterrorism regime and concludes that the implementation of the AU counterterrorism framework is counterproductive.